Cinderella across Cultures : New Directions and Interdisciplinary Perspectives - Woźniak, Monika; Lathey, Gillian, 1949-; Dutheil de la Rochere, Martine Hennard (Book collections on Project MUSE., 2016)
"This book examplifies the interdisciplinary and transnational discourse of contemporary fairy-tale studies that seeks to foreground a fairy-tale text's situatedness as well as to historicize its intertextuality. Considering Cinderella as a soical text means to approach its refashioning across languages, media, and cultures, as seen in the contributions that focus on translation and adaptation; to focus on how fairy-tale discourses inform our understanding of various societies and cultures, with essays on how producing and interpreting Cinderella texts are intertwined with assumptions about family, sexuality, gender, childhood, and nation; and to treat material objects in fairy tales, like glass, and fairy-tale ephemera, like posters, as cultural texts. The essays collectively provide new insights into contextualizing, retelling, and reimag(in)ing Cinderella, and, though they wisely do not aim for a global survye, they do engage cultural traditions that, while remaining rooted in a Euro-American context, decenter the Basile-Perrault-Grimms-Disney geneaology. In doing so, the editors and contributors of this volume deploy a keen awareness of the cultural work that translation, as process and trope, does in the production of and responses to Cinderella texts, thus significantly advancing a culture of translation in fairy-tale studies."